2015
DOI: 10.1007/s11031-015-9494-x
|View full text |Cite
|
Sign up to set email alerts
|

Attuned to the positive? Awareness and responsiveness to others’ positive emotion experience and display

Abstract: Positive emotions are implicated in affiliation and cooperation processes that are central to human social life. For this reason, we hypothesized that people should be highly aware of and responsive to the positive emotions of others. Study 1 examined awareness by testing the accuracy with which perceivers tracked others' positive emotions. Study 2 examined responsiveness by testing whether positive emotions were predictive of perceivers responding to new relationship opportunity. In Study 1, multilevel analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Research has shown that affiliation processes within close relationships, such as disclosing thoughts and feelings and providing/receiving social support, help relieve anxiety and reduce negative affect (Jakubiak & Feeney, ; Kane, Slatcher, Reynolds, Repetti, & Robles, ; Slatcher, Robles, Repetti, & Fellows, ). Furthermore, experiences of joy, contentment, and gratitude can promote relational well‐being by increasing trust and solidifying bonds (Campos, Schoebi, Gonzaga, Gable & Keltner, ; Kubacka, Finkenauer, Rusbult, & Keijsers, ). In contrast, relationship experiences such as resentment, secrecy, and conflict can lead to worry, hostility, and other forms of negative affect (Slepian, Chun, & Mason, ; Kiecolt‐Glaser et al, ).…”
Section: Discrete Emotional Experiencesmentioning
confidence: 99%
“…Research has shown that affiliation processes within close relationships, such as disclosing thoughts and feelings and providing/receiving social support, help relieve anxiety and reduce negative affect (Jakubiak & Feeney, ; Kane, Slatcher, Reynolds, Repetti, & Robles, ; Slatcher, Robles, Repetti, & Fellows, ). Furthermore, experiences of joy, contentment, and gratitude can promote relational well‐being by increasing trust and solidifying bonds (Campos, Schoebi, Gonzaga, Gable & Keltner, ; Kubacka, Finkenauer, Rusbult, & Keijsers, ). In contrast, relationship experiences such as resentment, secrecy, and conflict can lead to worry, hostility, and other forms of negative affect (Slepian, Chun, & Mason, ; Kiecolt‐Glaser et al, ).…”
Section: Discrete Emotional Experiencesmentioning
confidence: 99%
“…The fact the positive emotions are less critical for survival is not to deny the importance of their social functions. Positive emotions are involved in affiliation and cooperation and therefore important for adaptation ( Campos et al, 2015 ). Different positive emotions have specific functions – respond to material opportunities or social stimuli, facilitate playing new skills, encode novel information – that require distinct expressive signals to be effectively communicated ( Shiota et al, 2014 ).…”
Section: Hypothesis: Facial Dynamics and Body Representations Are Crimentioning
confidence: 99%
“…Relationships create opportunities for positive affective experiences, amplifying and sustaining the experience of positive emotions in relationships [31,32]. In turn, positive emotions foster closeness and strengthen connections in relationships [33], and through this pathway, they can positively influence our physiology [34]. Likewise, and possibly through accumulated experience of positive social connections [35], relationships can buffer against negative emotional experiences and facilitate the downregulation of negative emotions and stress [36,37].…”
Section: Affective Processesmentioning
confidence: 99%